Critical Analysis of Athlete Retirement from Sport (Laisvalaikio tyrimai, 2019)
Object of the analysis. Investigation problem. Athletes' retirement from sports activities and their life after the end of their sports career is relevant in scientific, practical and social terms. The purpose of this study was to provide an overview of scientific studies on athletes’ retirement from sport and how it relates to their life after their carrier in sports.Research methods. The analysis of scientific literature revealed that the main reasons for athletes to finish their careers in sports were trauma, health-related problems or age. Retirement can also be associated with family or family planning. Sports career termination is discussed in two ways, when one retires from sport voluntarily and when one is forced to do so. Voluntary retirement for athletes is usually a planned event and thus most often it does not have a negative impact on their future life. These athletes tend to choose a family over their sports carriers, continue their education or go to work in sports related sectors. Another important factor is athletic identity. Athletes with strong athletic identity during their sports careers tend to have better social life after their retirement. These athletes also tend to have a strong athletic identity after their careers, thus they are less likely to experience stress or depressive symptoms due to their sports career termination. Forced retirement from sports career is usually due to career-ending injuries. Such career outcome is associated with greater short-term and long-term problems in the post-sport transition period. Since athletic careers are strongly controlled by others, the unforeseen outcomes of an unexpected sports career termination results in negative consequences that are related to increased personal responsibility for their further actions. This becomes a greater problem for those athletes that have a higher level of athletic identity as it results in anxiety and depression. Therefore, forced retirement from a sports career is considered to be the most troublesome and worrying problem in the field.Outcomes and conclusions An examination of research literature focused on athlete’s retirement suggests that termination of a sports career is an important event the consequences of which depend on whether it ends by own choice or not. Since the planned retirement from the sports career is less challenging, it is important to help athletes prepare for this stage of their lives. Additionally, it is crucial to focus all efforts on creating a support system for athletes who were forced to end their athletic careers.Keywords: athletic carrier, retirement, life after sport.